2015
DOI: 10.1039/c5ta02780b
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of a mechanically robust superhydrophobic acrylic polyurethane coating

Abstract: A mechanically robust superhydrophobic coating was facilely prepared based on bi-component acrylic polyurethane and fluoroalkyl silane modified silicas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 43 publications
0
46
0
1
Order By: Relevance
“…[35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion. 27,29,[41][42][43] Besides, the mechanical stability may be simply due to the fact that the coating thickness is too thick to be worn out completely to expose the substrate surface underneath the superhydrophobic coating. The relationship between the wear resistance and thickness of the coating has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion. 27,29,[41][42][43] Besides, the mechanical stability may be simply due to the fact that the coating thickness is too thick to be worn out completely to expose the substrate surface underneath the superhydrophobic coating. The relationship between the wear resistance and thickness of the coating has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In practical environments, especially when a surface is used in the open air, long term exposure to UV, high air humidity and large temperature differences, must be taken into consideration when considering the stability of the surface. Durable superhydrophobic coatings have been reported recently, 26 such as acrylic polyurethane based coating, 27 textured surface obtained by chemical etching, 28,29 surfaces template from innately microstructured hydrogel matrix, 30 block-copolymer-based thin-film patterning, 31 combination of rodlike palygorskite and organosilanes via spray-coating, 32 fluorine-free polysiloxane/multiwalled carbon nanotubes, 33 titanium dioxide materials with special wettability, 34 or various coatings fabricated on fabrics/sponges/cotton. [35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many reports demonstrated that 2D PU membrane was prepared by spray-coating methods for oil/ water separation. [32][33][34][35] For example, Li et al 33,34 reported that the membrane was prepared through spraying TiO 2 nanoparticles (or ZnO nanoparticles) and PU mixture solutions onto copper mesh (or stainless steel mesh) for oil/water separation, where only the water permeated through the mesh while the oil was repelled on the mesh. Here, the role of waterborne PU was to increase the cohesive strength between TiO 2 nanoparticles (or ZnO nanoparticles) and copper mesh (or stainless steel mesh), thus increasing the stability of oil/water separation cycles.…”
Section: Spray-coating Methodsmentioning
confidence: 99%
“…Polyurethane (PU) is a multi‐purpose synthetic resin with various product forms. It is widely used in transportation, construction, electronic equipment, synthetic leather, healthcare and other fields, and adopts the form of foam plastics, elastomers, coatings, adhesives, waterproof materials etc. PU coating has outstanding properties such as good flexibility, wear resistance, high strength and strong adhesion, but it limits actual extensive applications in many industries because of its low thermal stability and mechanical strength .…”
Section: Introductionmentioning
confidence: 99%